A new formulation of fk for the PANS model. Issue 5 (4th May 2019) - Davidson, Lars; Friess, Christophe
ABSTRACT: The partially averaged Navier–Stokes (PANS) model, proposed in Girimaji [Partially-averaged Navier-Stokes model for turbulence: a Reynolds-averaged Navier-Stokes to direct numerical simulation bridging method. ASME J Appl Mech. 2006;73(3):413–421], can be used to simulate turbulent flows either as a RANS, LES or DNS. The PANS model includes f k which denotes the ratio of modelled to total kinetic energy. In RANS, f k = 1, and in DNS it goes to zero. In the present study we propose a new formulation for f k based on the H -equivalence introduced by Friess et al. [Toward an equivalence criterion for hybrid RANS/LES methods. Int J Heat Fluid Flow. 2015;122:233–246]. In this formulation the expression of f k is derived to mimic DES. This new formulation behaves very much like classic DES, even though the two formulations use different mechanisms to separate modelled and resolved scales. They show very similar performance in separated flows as well as in attached boundary layers. Moreover, the new formulation exhibits similar robustness features as DES.